Validitas LKPD elektronik berbasis Liveworksheet pada konsep virus untuk meningkatkan keterampilan berpikir kritis siswa jenjang SMA: Liveworksheet based electronic worksheet validity on virus concepts to improve critical thinking of High School Students - Zainab Zainab; Kaspul Kaspul; Bunda Halang (HAFECS PRESS, 2022)
Pendidikan abad ke-21 menuntut keterampilan berpikir kritis peserta didik. Cara yang dapat dilakukan guru untuk melatih kerampilan ini adalah dengan menyediakan LKPD elektronik. Tujuan dari penelitian ini adalah untuk mendiskripsikan validitas, kepraktisan dan keefektifan LKPD elektronik. Metode penelitian menggunakan desain Evaluasi Formatif Tessmer, dengan tahapan 1) self evaluation, 2) expert review, 3) one to one evaluation dan 4) small group evaluation. Subjek uji validitas yaitu 2 orang dosen pembimbing dan 1 guru Biologi jenjang SMA, subjek uji perorangan yaitu 4 orang siswa kelas X SMA dan subjek uji kelompok kecil yaitu 6 orang siswa kelas X SMA. Data didapatkan melalui instrumen penelitian berupa lembar penilaian validitas, kepraktisan isi dan harapan, serta keefektifan harapan. Teknik pengumpulan data menggunakan lembar penilaian. Hasil dari penelitian menyatakan: 1) validitas LKPD elektronik memperoleh skor rata-rata 3,66 termasuk kategori valid; 2) kepraktisan isi LKPD elektronik memperoleh skor rata-rata 3,90 termasuk kategori baik, kepraktisan harapan LKPD elaktronik memperoleh persentase 98,79% dengan kategori sangat baik; dan 3) keefektifan LKPD elektronik memiliki kategori sangat baik pada keterampilan interpretasi memiliki skor 86,32%, analisis memiliki skor 90,00%, evaluasi memiliki skor 91,88%, inferensi memiliki skor 88,89%, eksplanasi memiliki skor 90,41% dan pengaturan diri memiliki skor 87,83%. Abstract. 21st century education demands learners' critical thinking skills. Education is also required to create a generation of skilled uses of technology. One of the efforts that educators can make to train these skills is to provide electronic LKPD. Electronic LKPD is an innovation of learning devices as technology develops and is able to facilitate online learning due to the current pandemic. The purpose of this study is to describe the validity, practicality and effectiveness of electronic LKPD. The research method uses Tessmer's Formative Evaluation design, through stage 1) self evaluation, 2) expert review, 3) one-to-one evaluation and 4) small group evaluation. The validity test subject consists of 2 guidance lecturers and 1 high school biology teacher, an individual test subject consisting of 4 students of class X high school and a small group test subject consisting of 6 students of class X high school. Data is obtained from research instruments in the form of validity assessment sheets, content practicality, expectation practicality, and effectiveness of expectations. Data collection techniques using assessment sheets. The results of the study showed: 1) the validity of electronic LKPD based on validation results had an average score of 3.66 with a valid category; 2) Practicality of electronic LKPD content based on student response has an average score of 3.90 with good categories, practicality of electronic LKPD expectations based on student response has a percentage of 98.79% with excellent category; and 3) the effectiveness of electronic LKPD based on critical thinking skills assessment has excellent categories on interpretation skills with a score of 86.32%, analysis with a score of 90.00%, evaluation with a score of 91.88%, inference with a score of 88.89%, explanatory with a score of 90.41%, and self-regulation with a score of 87.83%.